AN ANALYSIS OF SYMBOLISM ON SATU SURO IN KERATON YOGYAKARTA - Monika Dian (JURNAL ILMIAH BAHASA DAN SASTRA, 2015)
Suro is the first day of the month of Javanese calendar, sura or suro which coincides with the first of Muharram in the Islamic calendar.One suro usually celebrated in the evening after sunset on the day before the date of the usually called Malam Satu Suro or the night a suro. Many kinds of symbols used on it. It is interesting to study Symbolism on Satu Suro in linguistics way, especially in semiotic. Therefore, the researcher has been interested in studying this problem by formulating four researcher problems such as: what are the functions of the ritual before the celebration of Satu Suro? Why ritual must be done before the celebration of the Suro? What are the functions of symbol which are used in celebrating Satu Suro? Why are symbols of Satu Suro reflected on celebrating Satu Suro? The research of this thesis is qualitative descriptive research. It is intended to describe about the symbols, and also the symbols meaning used in Satu Suro celebration. The instruments used in this study are documentation, observation, and interview. The analysis of the data includes studying and reading the theory. Understanding the data and then analyzing the terms and symbols meaning based on the theory. The researcher found that celebration Satu Suro in Yogyakarta Palace there are 5 Devotion or Lima Dharmabakti that must be done before the celebration of the Suro such as; Samadhi, Ruwatan, Clean the tomb, Alms Earth, and Sedekah. And there are 24 kinds of offerings that must be used in celebaring Satu Suro. Every symbol has the meaning.All these things must be done because they believe that if you miss the ritual alone, there will be a disaster. Finally, the researcher really hopes for the further researcher to complete this study to be perfect. In addition, the researcher hopes that this research can help other researcher who wants to continue or conduct research in the same field of the study or discuss about language aspect that occur in the Satu Suro celebration. And also the researcher hopes that further researcher can analyze literary devices used on Satu Suro celebration or the other ceremony on Javanese cultural especially in Yogyakarta.